2011
DOI: 10.1007/s00421-011-2173-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of a perceptual hyperthermia index to evaluate heat strain during treadmill exercise

Abstract: Fire suppression and rescue is a physiologically demanding occupation due to extreme external heat as well as the additional physical and thermal burden of the protective garments. The hot environment challenges body temperature homeostasis inducing heat stress. Accurate field assessment of hyperthermia is complex and unreliable. Purpose: The present investigation developed a perceptually based hyperthermia metric to measure physiologic exertional heat strain during treadmill exercise. Methods:Sixty-five (28.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 59 publications
1
19
0
1
Order By: Relevance
“…On this basis, the exposure limit of the PeSI ranging from 7 and 8 with the corresponding RPE-TS combinations towards the heavy level of physiological strain (3 < PSI HR ≤ 4) was obtained. Using the similar concept proposed by Gallagher et al (2012), RPE on the horizontal axis and TS on the vertical axis replacing the PeSI values were linked to each physiological strain level (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…On this basis, the exposure limit of the PeSI ranging from 7 and 8 with the corresponding RPE-TS combinations towards the heavy level of physiological strain (3 < PSI HR ≤ 4) was obtained. Using the similar concept proposed by Gallagher et al (2012), RPE on the horizontal axis and TS on the vertical axis replacing the PeSI values were linked to each physiological strain level (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…When the core body temperature continues to rise, central nervous system dysfunction will appear. This phase is called heat stroke [21,22]. This section of the questionnaire was dedicated to gathering opinions about heat illness experienced during firefighting.…”
Section: Evaluation Of Fpc In Current Usementioning
confidence: 99%
“…Some studies have utilized training drills with environmental temperatures less than 100°C in a live-fire burn structure to simulate fire ground activities [18][19][20][21][22]. More commonly, research groups have used a treadmill protocol in a temperature-controlled ( 25°C to 50°C) room [23][24][25][26][27][28]. While Selkirk and McLellan have shown that the physiological responses to activity in fire fighting PPE is affected by the ambient temperature of the testing environment, there are limited data available upon which to base the representative thermal conditions.…”
Section: Introductionmentioning
confidence: 99%